ANALISIS YURIDIS SISTEM MAGANG CALON NOTARIS BERDASARKAN RUANG LINGKUP KETENAGAKERJAAN - I Gusti Nyoman Yonatan (Penerbit Universitas Atma Jaya Yogyakarta, 2026)
Prospective Notaries are required to undergo an internship in order to be appointed as Notaries. There is no legal basis governing internships for prospective Notaries, but there is a legal basis related to internships in the realm of employment law. There needs to be an interpretation and discovery of the law so that regulations in the field of employment can apply in the field of notaries. The objectives of this study are twofold. First, to find out and examine whether or not the legislation on employment can apply to the implementation of internships for prospective Notaries. Second, to find out and examine the rights and obligations of Notaries Receiving Interns towards interns. The type of research used is normative juridical with a statutory regulatory approach. The results of the study indicate that legislation on employment can apply to the implementation of internships for prospective Notaries with legal interpretation. The rights and obligations of Notaries Receiving Interns can be found in the Regulations of the Indonesian Notary Association and the Regulations of the Minister of Manpower.